Trends in Hip Resection Arthroplasty in the Medicare Patient Population from 2005 to 2012 - Merose, Omri; Zachwieja, Erik; Rosas, Samuel; Kurowicki, Jennifer; Grau, Luis C.; Hernandez, Victor H. (The Journal of Hip Surgery, 2017)
Hip resection arthroplasty (HRA) is a relatively uncommon, yet viable surgical procedure originally developed by Girdlestone for osteomyelitis of the proximal femur. Currently, HRA is primarily indicated as a salvage procedure after a failed total hip arthroplasty. Despite a continuous rise in the rates of primary and revision hip arthroplasty, there is a lack of published evidence regarding the extent of HRA's current use and its recent trends. We sought to provide an epidemiological description of the recent utilization patterns of HRA in the United States. A level of evidence IV, retrospective case series review of the entire Medicare files between 2005 and 2012 was conducted through the use of current procedural terminology codes and International Classification of Disease ninth edition codes. Linear regressions and chi-square tests were used for analysis. Subgroup analysis was performed by patient age. The total number of HRAs performed between 2005 and 2012 significantly decreased from 4,248 to 3,872 (p = 0.025). There was a significant increase in the annual incidence of HRA among patients younger than 65 years (p = 0.027; 9% increase) and patients 65 to 69 years old (p = 0.007; 22% increase), constituting 43% of the total patients. There was a significant decrease in HRA incidence among patients 80 to 84 years old (p = 0.001; 32% decrease) and patients 85 years old and over (p = 0.002; 24% decrease). Geographic analysis demonstrated the most HRA procedures were performed in the South, whereas gender focused analysis demonstrated a statistically significant decrease in HRA incidence for females (p = 0.003; 6% decrease) and a significant increase in incidence for males (p = 0.003; 7% increase). The overall annual incidence of HRA performed in the Medicare patient population has significantly decreased in recent years. However, this conceals an increased incidence among the relatively younger patient population. Potential causes for these opposing trends include changes in rates of revision surgery, alternative indications for surgery, advances in hardware, and surgeon expertise. This was a level of evidence IV, retrospective case series study.
Keywords: hip resection arthroplasty; hip; arthroplasty; epidemiology; infection